Person‐years of life lost and lost earnings from cigarette smoking‐attributable cancer deaths, United States, 2019. Issue 12 (10th August 2022) - Islami, Farhad; Marlow, Emily C.; Zhao, Jingxuan; Wiese, Daniel; Asare, Samuel; Bandi, Priti; Thomson, Blake; Zheng, Zhiyuan; Nargis, Nigar; Yabroff, K. Robin; Jemal, Ahmedin
Abstract: State‐specific information on lost earnings due to smoking‐attributable cancer deaths to inform and advocate for tobacco control policies is lacking. We estimated person‐years of life lost (PYLL) and lost earnings due to cigarette smoking‐attributable cancer deaths in the United States nationally and by state. Proportions and numbers of cigarette smoking‐attributable cancer deaths and associated PYLL among individuals aged 25 to 79 years in 2019 were calculated and combined with annual median earnings to estimate lost earnings attributable to cigarette smoking. In 2019, estimated total PYLL and lost earnings associated with cigarette smoking‐attributable cancer deaths in ages 25 to 79 years in the United States were 2 188 195 (95% CI, 2 148 707‐2 231 538) PYLL and $20.9 billion ($20.0 billion‐$21.7 billion), respectively. States with the highest overall age‐standardized PYLL and lost earning rates generally were in the South and Midwest. The estimated rate per 100 000 population ranged from 352 (339‐366) in Utah to 1337 (1310‐1367) in West Virginia for PYLL and from $4.3 million ($3.5 million‐$5.2 million) in Idaho to $14.8 million ($10.6 million‐$20.7 million) in Missouri for lost earnings. If age‐specific PYLL and lost earning rates in Utah had been achieved by all states, 58.2% (57.0%‐59.5%) of the estimated total PYLL (1 274 178; 1 242 218‐1 306 685 PYLL) and 50.5% (34.2%‐62.4%) of lost earnings ($10.5 billion; $7.1 billion‐$13.1 billion) in 2019 nationally would have been avoided. Lost earnings due to smoking‐attributable cancer deaths are substantial in the United States and are highest in states with weaker tobacco control policies. Abstract : What's new? While smoking is a leading preventable cause of cancer death in the United States, the impact on life expectancy and economic burden of smoking‐attributable cancer deaths remains uncertain. Here, using state‐specific population data and census data on annual median earnings, the authors estimated the number of smoking‐attributable deaths and potentially avoidable losses in earnings for 2019. Analyses indicate that in 2019, for persons age 25 to 79, cigarette smoking‐attributable cancer deaths accounted for 2.2 million person‐years of life lost (PYLL) and approximately $21 billion in lost earnings. Analyses further suggest that greater than half of PYLL and lost earnings were avoidable.